2022
DOI: 10.1002/ijc.33995
|View full text |Cite
|
Sign up to set email alerts
|

The single‐cell transcriptional landscape of lung carcinoid tumors

Abstract: Lung carcinoid tumors, also referred to as pulmonary neuroendocrine tumors or lung carcinoids, are rare neoplasms of the lung with a more favorable prognosis than other subtypes of lung cancer. Still, some patients suffer from relapsed disease and metastatic spread. Several recent single‐cell studies have provided detailed insights into the cellular heterogeneity of more common lung cancers, such as adeno‐ and squamous cell carcinoma. However, the characteristics of lung carcinoids on the single‐cell level are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
(126 reference statements)
0
9
0
Order By: Relevance
“…More interestingly, they found the heterogeneity of tumor cells and their corresponding TIMEs inside NECs: cell clusters with the NE phenotype had a colder TIME, characterized by lower immune scores and fewer enrichments of immune response-related pathways than those with non-NED phenotype, which emphasized the close correlation between the NE phenotype and TIME features, even inside NENs. In lung NETs (carcinoids), Bischoff et al [17] found a comparable lymphoid microenvironment as normal tissues, while the noninflammatory monocyte-derived myeloid cells increased prominently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More interestingly, they found the heterogeneity of tumor cells and their corresponding TIMEs inside NECs: cell clusters with the NE phenotype had a colder TIME, characterized by lower immune scores and fewer enrichments of immune response-related pathways than those with non-NED phenotype, which emphasized the close correlation between the NE phenotype and TIME features, even inside NENs. In lung NETs (carcinoids), Bischoff et al [17] found a comparable lymphoid microenvironment as normal tissues, while the noninflammatory monocyte-derived myeloid cells increased prominently.…”
Section: Discussionmentioning
confidence: 99%
“…Since TIMEs are surrounded by tumor cells and tissue fluid, their composition and function are susceptible to tumor-specific factors that help different tumors shape their distinctive TIMEs. This phenomenon has been found in various types and grades of neuroendocrine neoplasms (NENs) [17][18][19][20]. However, regarding non-NENs but where ectopic NED occurred, such as GC-NED, their TIMEs have not been touched, and whether GC-NED harbored a different TIME from that of PGC was unknown.…”
Section: Introductionmentioning
confidence: 99%
“…First, pulmonary NETs that express membrane EGFR might be amenable to therapeutic strategies that either directly target this receptor, or that target receptor-mediated downstream signaling pathways and that are currently approved for the treatment of other tumor types. There have been reports of EGFR expression in pulmonary NETs, but these studies were unable to determine whether receptor expression played a functional role in promoting the growth or survival of these tumors (Bago-Horvath et al, 2012; Bischoff et al, 2022; Rickman et al, 2009; Rusch et al, 1996). Our data argue the expression of EGFR is indicative, to some degree, of EGF-dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, there was not a statistically significant difference in survival rates between patients with and without simultaneous pathological findings. It has been reported that monocyte-derived myeloid cells in lung carcinoid tissues have equal to slightly lower expression scores of numerous gene profiles associated with inflammation and the immune response when compared to normal tissues, indicating that the lung carcinoid immune microenvironment is predominated by non-inflammatory monocyte-derived myeloid cells, without mentioning if this finding is associated with better outcomes ( 43 ). However, it remains to be determined whether this finding is associated with improved outcomes.…”
Section: Discussionmentioning
confidence: 99%